An Odontometric Investigation of the Affinities of the Nazlet Khater Specimen to Prehistoric, Protohistoric and Modern African Populations - Ron Pinhasi (Dental Anthropology Association, 1998)
This study scrutinizes the affinities of a 33,000-year-old skeleton from Nazler Khater, Egypt, to various prehistoric African populations. The comparative material consists of 231 individuals, ranging in time from the Middle Pleistocene to recent and restricted in space to the African continent and Southern Levant. Possible affinities were first examined with the application of univariate, and bivariate, statistics. Subsequently, principal components analysis and cluster analysis are performed on mean data from 29 populations, utilizing a selected set of tooth dimensions. The results indicate a strong association between some of the sub-Saharan Middle Stone Age (MSA) specimens and he Nazlet Khater skeleton. No clear discrimination was reached between the various African and Levantine populations. The significant differences between male and female mean data factor scores on the first principal component indicate that sexual dimorphism accounts for a large portion of the observed variability in size.